2014
DOI: 10.2105/ajph.2013.301573
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Death in Asian Americans

Abstract: Objective To investigate the association between body mass index (BMI) and mortality among Asian Americans Methods We pooled data from prospective cohort studies that included 20,672 Asian American adults with no history of cancer or heart disease at baseline. Hazard ratios and 95% confidence intervals (CI) were estimated using Cox proportional hazards models. Results A high, but not low, BMI was associated with an increased risk of total mortality among individuals 35–69 years old. BMI was not related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
6
20
1
1
Order By: Relevance
“…Even more recently, Park et al 30 used Cox proportional hazards models to estimate mortality among Asian Americans in different BMI categories. Data were pooled from previously published prospective cohort studies.…”
Section: Alternative Anthropometric Standards For Ethnic and Racial Mmentioning
confidence: 99%
“…Even more recently, Park et al 30 used Cox proportional hazards models to estimate mortality among Asian Americans in different BMI categories. Data were pooled from previously published prospective cohort studies.…”
Section: Alternative Anthropometric Standards For Ethnic and Racial Mmentioning
confidence: 99%
“…Y. Fang et al, 2014), and eating disorder symptoms (Kroon Van Diest, Tartakovsky, Stachon, Pettit, & Perez, 2014). For example, Park et al (2014) found that acculturative stress was positively associated with alcohol use, but only for Vietnamese immigrants, and not for Chinese and Filipino immigrants in the United States, which may be because Vietnamese immigrants have less prior exposure to the American culture and a relatively short history of immigration. The results underscored the importance of considering the heterogeneity of Asian Americans in research on alcohol use.…”
Section: Resultsmentioning
confidence: 96%
“…V. Chung et al, 2014; Tiedje et al, 2014; S. S. Yi, Ruff, Jung, & Waddell, 2014), body mass and obesity ( n = 3; Cassel, Braun, Ka’opua, Soa, & Nigg, 2014; Franzen-Castle & Smith, 2014; Y. Park et al, 2014), body image and eating disorders ( n = 6; Chang, Yu, & Kahle, 2014; H.-L. Cheng, 2014; de Guzman & Nishina, 2014; Kelly, Cotter, Tanofsky-Kraff, & Mazzeo, 2014; Masuda, Le, & Cohen, 2014; Smart & Tsong, 2014), and diabetes ( n = 4; Inouye, Matsuura, Li, Castro, & Leake, 2014; Qiao et al, 2014; T.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Hsu et al (2015) states that the lower thresholds should not redefine BMI thresholds for overweight and obesity thresholds in relationship to mortality or morbidity in Asian Americans. Moreover, a recent study did not find an increased risk of total mortality among Asian Americans within the BMI range of 20 to < 25 kg/m 2 (Park et al, 2014). Mounting evidence also suggests that not all obese subjects are at increased cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%